Development Of A Smart Grid System For Renewable Energy Integration - Michael Smith; Olivia Brown; Sophia Taylor (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This study presents the development of a smart grid system designed to efficiently integrate renewable energy sources into the existing electrical grid. The proposed system employs advanced communication technologies and real-time data analytics to optimize energy distribution and consumption. A simulation model was created to evaluate the system's performance under various scenarios, demonstrating significant improvements in energy efficiency and reliability. The findings indicate that the smart grid system can enhance the stability of the electrical network while promoting the use of sustainable energy sources.